Employee Mental Health and Workplace Well-Being Programs in Oil Services Firms: Evidence from Port Harcourt, Nigeria - Olayinka Kayode Osho (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examines the influence of workplace well-being programs on employee mental health outcomes in oil services firms in Port Harcourt, Nigeria. Despite growing discourse on occupational health, the Nigerian petroleum services sector remains underexplored regarding the effectiveness of structured organizational interventions in mitigating employee burnout and psychological distress. Drawing on the Job Demands-Resources (JD-R) Model and the Conservation of Resources (COR) Theory, the study adopted a cross-sectional survey research design. Primary data were gathered from 247 employees across three prominent oil services companies using a structured questionnaire. Simple linear regression analysis was employed to examine the hypothesized relationships. The findings revealed that Employee Assistance Programs (EAPs), workload management initiatives, and psychosocial support structures each exerted a statistically significant positive effect on employee mental health outcomes (p < 0.05). Specifically, EAPs accounted for 34.2% of the variance in mental health outcomes (R² = 0.342), workload management explained 28.7% (R² = 0.287), and psychosocial support structures accounted for 31.5% (R² = 0.315). These results underscore the critical need for oil services firms to institutionalize comprehensive and context-sensitive well-being programs that are responsive to the high-demand nature of the industry. The study contributes to the growing body of knowledge on organizational behavior and human resource management in the context of developing economies.